DNA Genotyping of Borneo Ironwood using M13 Universal Primer and SCAR Marker Development in Eusideroxylon zwageri - Ho Wei, Seng; Yii Ai, Siew; Lee Shiat, Mei; Cheksum, Tawan; Isa, Ipor; Pang Shek, Ling; Julaihi, Abdullah (Ecological Association of Malaysia, 2014)
Borneo Ironwood, consists of two species, i.e. Eusideroxylon zwageri and Potoxylon melagangai, is the most well known durable tropical hardwood timber tree of Borneo. Both species are morphologically similar, except the wood characteristics. This has resulted in taxonomic difference between them. We used PCR with M13 universal primer to determine the genetic relatedness and SCAR marker to distinguish both species. Cluster analysis grouped both species into two major clusters, suggesting that there are two genetically distantly related species. One diagnostic band (locus M13-16) was successfully converted to SCAR marker. A single fragment (720 bp) was amplified in all E. zwageri individuals but completely absent in P. melagangai. Differentiating the species by SCAR marker is very useful for screening large numbers of Borneo Ironwood seedlings collected from natural populations. The identification of individuals at species level constitutes one of the first basics in any effective conservation programme. In fact, the Borneo Ironwood has been counted as one of the endangered species in Sarawak.